Radiotherapy Combined with Chemotherapy for Regional Lymph Node Recurrence in Gastric Cancer - Cai, Liang (Cancer Manag Res, 2020)
PURPOSE: Regional lymph node recurrence (RLNR) in gastric cancer is uncommon. We investigated the effects of radiotherapy combined with chemotherapy against limited RLNR and analyzed the regularity of regional lymph node recurrence and metastasis. PATIENTS AND METHODS: This retrospective study included 34 gastric cancer patients with limited RLNR after D2 lymphadenectomy between January 2012 and May 2018. All patients received systemic chemotherapy and local radiotherapy with median dose of 52.5 Gy (30–66 Gy in fractions of 1.8–3.0 Gy daily, five times weekly). All sites of recurrent and metastatic lymph nodes were collected and analyzed. RESULTS: The median follow-up was 19 months (range 7–60 months). After treatment, complete response and partial response were observed in 32.4% and 55.9% of patients, respectively. The median overall survival (OS) and progression-free survival (PFS) were 18 months and 13 months. On multivariate analysis, age (≤60 vs >60) was associated with a significantly better OS (p = 0.025) and radiation dose (<54 Gy vs ≥54 Gy) was considered as an independent prognostic factor for PFS (p = 0.000). During radiotherapy, three patients developed grade 3 gastrointestinal toxicity, and no deaths were related to the treatments. The most commonly metastatic lymph nodes were the No. 4, No. 3, No. 6, No. 5, No. 7, No. 9, and No. 8 nodes; the recurrent lymph nodes were mainly located in the No. 16b, No. 16a, No. 9, No. 14, No. 7, No. 13, and No. 8 nodes. CONCLUSION: The selected gastric cancer patients with limited RLNR may benefit from radiotherapy combined with chemotherapy. High-dose radiotherapy (≥54 Gy) lead to better PFS and tend to extend OS. The major lymph node recurrence sites were in the gastric vascular region (especially No. 16a/b nodes).